Comparison of Empirical and Kinetic Modeling of the Photocatalytic Oxidation of Cyanide - Marugan, Javier (2007)
An intrinsic kinetic model based on the reaction mechanism of the photocatalytic oxidation of cyanide with TiO2 has been developed and applied to the results of experiments carried out using different catalyst concentrations, initial concentrations of cyanide and incident radiation fluxes. The results of the kinetic modeling have been compared with the use of an empirical model equation generated following the response surface methodology; a statistical procedure to correlate the influence of several factors on a response variable. The kinetic model reproduces the experimental data with a relative error below 13%, slightly lower than that obtained with the empirical model equation. In contrast with the latter, the kinetic model is based on the intrinsic photocatalytic reaction mechanism and takes into account the radiation profiles inside the photoreactor. Consequently, after validating the model in a broad range of experimental conditions, it could be applied to any other reactor configuration, allowing the simulation and optimization of the radiation and reaction rate fields with scalingup and photoreactor design purposes.